Efektivitas Penggunaan Laboratorium Virtual Berbasis Keterampilan Proses Sains Terintegrasi Zoom Meeting untuk Meningkatkan Pemahaman Konsep Fisika Siswa Pada Masa Pandemi Covid-19 - Kristina Sara; Ilyas Ilyas; An Nisaa Al Mu’min Liu (Postgraduate, University of Mataram, 2022)
This study aims to describe the improvement in students understanding of physics concepts after using a virtual laboratory based on integrated science process skills zoom cloud meeting in class XA SMAN 1 Ende which totals 36 students. This research is quantitative descriptive research This type of research is quantitative descriptive research. Considering that the number of research groups is only one group, the research design used is one pretest-posttest design group. The research mechanism is carried out through four stages, namely pretest, providing treatment in the form of practicum using virtual laboratories based on integrated science process skills zoom meeting, and providing posttests to find out the increase in scores in solving kinematics concept problems. The data collected are pretest and posttest scores, effectiveness analysis techniques using the N-Gain test.Â The results showed that the increase in students understanding of concepts averaged 4.27. At the time of the pretest, the average score of students understanding of concepts was 4.47 while the posttest result was 8.75. while the N-Gain value is 0.77. The N-Gain value of 0.77 belongs to the high category. Meanwhile, if it is concentrated at 77 percent, it means that the use of virtual labs based on integrated science process skills zoom meetings is effective in increasing students understanding of concepts.